Efficiency increasing of a shipyard power supply system - Beley V. F.; Korotkikh K. V. (Vestnik MGTU)
The development of the shipbuilding industry involves increasing the competitiveness of manufactured products, replacing obsolete electrical equipment, and increasing the efficiency of power supply systems. The introduction of the latest technologies reduces the weight and size of equipment, expands their functionality, but these technologies are based on nonlinear and asymmetrical power consumers, which causes a negative impact on the power grid. The power supply system of the Baltic Shipyard "Yantar" is characterized by a significant share of nonlinear, asymmetrical loads, often single-phase. An integrated approach to the analysis of the plant's power supply system included experimental studies of nonlinear power consumers, during which a high level of higher current harmonics (3rd, 5th and 7th orders) was established. One of the effective methods for reducing zero-sequence voltage asymmetry is to replace a transformer with a Y/Y0 winding connection diagram with a Δ/Y0 diagram. Circuit and technological solutions (separation of nonlinear loads to a separate bus system; increasing the phase of semiconductor converters; connecting a nonlinear load to a system with greater short-circuit power) and filtering devices (narrow-band filters, filter-balancing devices and active filters) are used to increase the efficiency of the power supply system when it operates under conditions of increasing distorting loads.